Analisis Pengaruh Transformational Leadership Terhadap Organizational Citizenship Behavior Dengan Kepuasan Kerja Sebagai Variabel Intervening.(Studi Kasus Pada Kantor Pelayanan Pajak Pratama Karanganyar) - Kadarini, Swasti; , Drs. M. Farid Wajdi, Ph.D; , IhwanSusilo, SE.,M.Si., Ph.D (2017)
This research aims to analyze the effect of transformational leadership on organizational citizenship behavior in diation by job satisfaction. Samples were determined by random sampling technique, the responses of 97 respondents on KPP Pratama Karanganyar's officials. Mechanical analysis using linear regression and path analysis. Based on the test of instrument all variables are valid and reliable. From the data analysis' findings, it can concluded that nsformational Leadership has a positive significant affect on anizational Citizenship Behavior, partially mediated by job atisfaction. Seen coefficient (Rsquare) it can be concluded that amounted to 30,7% while the rest influenced by other factors outside the study variables.